Digital Pop Up Learning Media for Early Childhood Cognitive Development - Anis Khamidah; Norma Ita Sholichah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
Education in the era of highly rapid digital development is a challenge for educators. Technology development encourages teachers to reform teaching and learning process and create updated education. This research aims to develop a digital Pop Up learning media for cognitive development of children aged 5-6 year-old. This was Research and Development (R&D) research using Borg and Gall development model. The developed media was validated by two experts and categorized highly valid (98%) by media expert and valid (87.5%) by material expert. Result of limited tried out involving 10 students of group B was 80% and categorized valid. Based on the finding, digital Pop Up media was effective as an interesting learning supporting means and appropriate to the development of 4.0 revolution era.┬á┬á